Pengaruh Pendidikan Perkoperasian dan Kualitas Pelayanan Koperasi Simpan Pinjam Terhadap Partisipasi Anggota di KPN Depdikbudcam Padang Selatan - Rahmayuni Alfajri; Syamwil Sya (Universitas Negeri Padang, 2022)
The main purpose from this study is to investigates (1) the effect of cooperative education and the quality of cooperative services on member involvement. (2) to ascertain the influence of cooperative education. (3) to ascertain the influence of cooperative service quality on KSP membership at KPN Depdikbudcam South Padang. This is known as ex-post facto research. The population of this study were all 39 members. The sampling technique employed in this study was census sampling or total sampling, which meant that the complete population was used as the research sample, resulting in a total sample size of 39 persons. Techniques for data collecting include questionnaires and documentation. (1) Cooperative education is critical for member engagement in KSP at KPN Depdikbudcam South Padang, according to the findings of this study. (2) concurrently, the cooperative service quality influences member involvement, and partially (t-test), the cooperative service quality does not affect member participation significantly. (3) member involvement in KSP at KPN Depdikbudcam Padang Selatan is significantly influenced by cooperative education and service quality Keywords : cooperative education, service quality, member participation